MULHERES NO FOTOJORNALISMO: Uma análise cultural da relação entre identidades de gênero e a prática do fotojornalismo na contemporaneidade - SILVA, NATHÁLIA CUNHA DA (2017)
This is a study about the cultural and historical influence of the social attributed gender roles on the access and development of women photojournalists in São Paulo city. The research aims to understand how women photographers work in press and perceive their own professional practices in the contemporary setting. The theoretical framework is based on Cultural Studies in the feminist perspective, and post-structuralism, considering the power relations presents in the gender discourses in the photojournalism, according to Stuart Hall, Lipovetsky, Bourdieu, Judith Butler e Michael Foucault. Furthermore, the historical configuration and development of photojournalism takes place in consonance with the journalistic values, according to the definitions of Jorge Pedro Souza and Ciro Marcondes Filho. The methodology used is guided by the qualitative method, using semi-structured type interviews. The interviews were conducted with nine women who have photojournalism as their main activity, with formal and informal working relationships and divided into three age groups. The analysis procedure dealt with the work relations, the definition of professional self-image and the relations of work and family. The results point to the influence of gender roles on the historical construction of the stereotype of the activity as masculine, producing symbolic barriers to discouragement of female participation since the professional training, and indicated the permanence permeated by the demand for a productive and reproductive imbalance. The difficulty in reconciling the profession with the social division of gender roles is identified as one of the main obstacles to female participation, and the women photojournalists present performative gender resistances to re-signify the professional stereotype.